Regional Cross-Border Trade Facilitation and Infrastructure Study for Mashreq Countries - World Bank (Washington, DC, 2013)
Many opportunities for trade of the Mashreq (Iraq, Israel, Jordan, Kuwait, Lebanon and Syria) countries are being lost because of inefficient trade facilitation processes and procedures, and to a lesser extent because of underdeveloped transport infrastructure. Implementation of the Pan Arab Free Trade Agreement has substantially reduced formal trade barriers between the countries. There is today extensive knowledge on the institutional arrangements for such agencies that work best under different conditions. Trade facilitation and transport services are largely the responsibility of private operators, yet an increase in their effectiveness would come through this agency which would include both private and public sector representation. The institutional proposals included in the short and medium term action plans are designed to create this new context. Recent initiatives within the Arab League to establish sub-regional committees of transport ministers have a similar objective of bringing a more focused attention to addressing trade facilitation issues. The proposal for a corridor management system presented in this report builds on these initiatives and draws on the experience gained from the operation of management systems in other corridors. This study used two analytical tools to assess the major trade and transport impediments to increased trade.